Zastosowanie protokołu głośnego myślenia i retrospekcji w badaniach autorefleksji prz yszłych naucz ycieli jęz yka angielskiego - Witkowska, Magdalena (Neofilolog, 2010)
Think-aloud protocol (TAP) makes it possible to discover human thoughts while conducting a task, whilst retrospection enables us to uncover thoughts that emerge after the task has been completed. The content of thoughts has been a subject of research in psychology and recently in education. Discovering the content of teachers’ self-reflection may raise the understanding of what it means to educate teachers-to-be and how to help them become reflective practitioners. Applying TAP and retrospection appears a thought-provoking experience especially when it comes the procedure and outcome.